Mac OSX Mountain Lion - mmmSpivey, Dwight; Stewart, Roger (New York McGraw- Hill, 2013)
With this book you'll learn how to :surf the net,read email,write school reports,create spreadsheets,make movies,share photos,listen to music,synchronize contacts with your iphone,ipad,or ipod touch,watch DVDs,stay on time by making custom calenders,video chat, print documents, back up your computer, add external devices to your Mac,download items from the Internet,and much more
Includes index
3
Keywords: Computer Operating Systems; Computer Software